Inter Religious Tolerance Among the People of Elbasan - Ã‡eÃ§i, Nuredin (Richtmann Publishing, 2012)
A special place in this article is given to the description of inter religious tolerance, as one of the most important cultural valuesamong Albanians. Also this article aims to highlight that complexity of factors, which with their actions have conditioned the birth andexistence of the religious tolerance; not only in the city of Elbasan but also in its surrounding areas. Furthermore this article aims to showthrough facts and their interpretation the main characteristics of such an environment, in comparison to other Albanian territories.